(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Sanu C, Jeevith S, Sheeba TC. 2023. Ethnomedicinal knowledge used by Mullukurumbas of Nilgiris, Western Ghats, India. Asian J Ethnobiol 6: 118-129. Nilgiris is one of the biodiversity-rich areas in the Western Ghats, India, with six major groups of indigenous tribes, and Mullukuruba is one of the subtribes of Kurumbas. The present study aimed to document the ethnomedicinal knowledge among the Mullukurumba Tribe of Kallical, Cherangode Village of Nilgiris, Western Ghats. Most of the tribes in Nilgiris follow a close cultural ritual and traditional knowledge, including food and medicine. The field data were collected through interviews, observation, and documentation. The tribal people utilized 152 plant species belonging to 60 families. The life forms of the collected plants revealed that herbs constitute 53 species, followed by shrubs 44 species, trees 35 species, and climbers 20 species. Family-wise, Fabaceae dominated with 13 species, followed by Asteraceae 10 species, and Solanaceae included 8 species. The use category made by the tribal community were medicinal plants (70%), edible fruits (19%), and miscellaneous uses (11%). The plant species treat various illnesses, including piles, rheumatism, gynecological issues, dermatitis, and antidiarrheal and anti-diabetic conditions. Argyreia cuneata (Willd.) Ker Gawl., Cascabela thevetia (L.) Lippold, Coix lacryma-jobi L., Ixora coccinea L., Gloriosa superba L., Melastoma malabathricum L., and Plumeria alba L. were the most common plants used for rituals. Also, this study presented an updated checklist of medicinal plants used by the Mullukurumba Tribe.